The American automobile : - Georgano, Nick (Smithmark, 1992)
Georgano has produced many of these large-type automobile picture books that combine quality photography with informative text. This latest is a celebration of 100 years of the American automobile. The book offers nothing new in the way of automotive history. However, most of the excellent photographs were shot specifically for the project, and they capture the starkness of the antique vehicles and the outlandish designs of the Fifties, as well as the allure of modern cars today.